2018
DOI: 10.37358/mp.18.4.5079
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Heating on Surface Microhardness of Resin-based Materials for Direct Restoration

Abstract: The aim of this study was to evaluate and to compare the surface hardness of three types of resin-based materials used for direct restoration after heating at different temperatures. A giomer (Beautifil II, Shofu Dental), a compomer (Dyract eXtra, Dentsply Sirona) and a hybrid composite resin (Gaenial Posterior, GC Corporation) were selected for this study. Twenty disk-shaped specimens of each material were heated at room temperature (21�C), at 37�C, at 50�C and at 60�C. Vickers microhardness test was performe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…The provided table (Tables 3, 4) summarizes various studies on microhardness and fracture toughness. Out of the total 29 studies included, 16 demonstrate an increase in microhardness alone [3,8,9,12,13,15,16,17,18,19,21,22,23,25,27,28], while one shows an increase in fracture toughness alone [20]. Additionally, three studies reveal no statistically significant difference in microhardness values [5,10,30].…”
Section: Resultsmentioning
confidence: 97%
“…The provided table (Tables 3, 4) summarizes various studies on microhardness and fracture toughness. Out of the total 29 studies included, 16 demonstrate an increase in microhardness alone [3,8,9,12,13,15,16,17,18,19,21,22,23,25,27,28], while one shows an increase in fracture toughness alone [20]. Additionally, three studies reveal no statistically significant difference in microhardness values [5,10,30].…”
Section: Resultsmentioning
confidence: 97%
“…An study which compare the the interface between enamel surfaces at the level of pit and fissure and the sealant with different cleaning procedures, with or without acid etching show that Concise White Sealant achieves a better enamel sealing than Dyract Seal when the teeth are treated with air abrasion or air polishing followed by etching [8]. The microhydrid composite resins have a significantly higher hardness than nano-hybrid composites or compomers [9,10] and in another study on top and on bottom surfaces Dyract eXtra showed the lowest hardness values [11]. Beresescu and all considered that particular types of restoring materials should be used in particular situation, depending on the location of the surfaces and the elastic characteristics of the materials and tooth structure [12].…”
Section: Resultsmentioning
confidence: 99%
“…8,9 Research on the giomer surface microhardness in previous studies, shows that preheating treatment at 60°C has a higher hardness than 37°C. 10 Another previous research, showed that preheating treatment at 60°C could lead to decreased microleakage and better marginal adaptation to composite resins. 11 Based on previous research that provides preheating treatment so as to increase mechanical strength and minimize microleakage in composites, it encourages researchers to conduct research that has never been done before to determine the effect of preheating treatment temperature on the release of giomer's fluoride.…”
Section: Introductionmentioning
confidence: 97%